The Relationship of Application Diverse Food Consumtion to Nutritional Status Student at MTs Al Hidayah Jenu Tuban - Hafsah Amalia Fajar Syafriana; Annas Buanasita; Nuning Marina Pengge; Riezky Faisal Nugroho (Journal of Nutrition Explorations, 2023)
Adolescents are a vulnerable age group who are faced with nutritional problems, both undernutrition and over nutrition. One of the several prevention efforts that can be implemented to deal with this nutritional problem is by consuming a variety of foods. The aim of this study was to determine the relationship between the application of diverse food consumption and the nutritional status of students at MTs Al Hidayah Jenu Tuban. This type of observational analytic research uses a cross sectional approach, the number of samples is 50 respondents, the sampling technique uses proportional random sampling, the research time is October 2021 - January 2022 and statistical tests use the chi square test. Application of diverse food consumption that falls into the appropriate category (66%) and good nutritional status (66%). The statistical test results showed that there was a relationship between the application of various food consumption and nutritional status (p=0.000). There is a relationship between the application of the consumption of a variety of foods to nutritional status, so it is expected to be able to apply the consumption of a variety of foods in daily life in accordance with recommended portions.